PENERAPAN PEMBELAJARAN MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SD NEGERI 002 RAMBAH 1 TAHUN PELAJARAN 2014/2015 - Hj., Darmawati (Edu Research, 2016)
Expected competencies in science learning requires students to maximize learning. To achieve these objectives required a great effort from the teachers and students. Strategies and learning model that has been used so far have not been able to increase the activity and student learning outcomes. The work done to overcome this problem with the application of multimedia learning. The results showed that learning by using multimedia to improve learning outcomes in the material science of natural events and natural resources in the classroom VA SD Negeri 002 Rambah, which is in the initial conditions before the results of actions by the average value of 77.31 (enough). In the first cycle by using multimedia to an increase so that the average value of the class into 85.19 (good). In the second cycle showed an increase in average earned 85.96 (good). Classical learning completeness students has increased that the first cycle of 76.92% (enough) increased in the second cycle into 88.46% (good), average student activity ranging from the first cycle to the secondcycle which is 94.47% (excellent ) with very good category. The average teacher activity first cycle that 87.5% (good) and cycle II had risen to 96% (excellent).